The Role of Intellectual Property Law in Increasing Science Education Capacity in Indonesia - Diana Tantri Cahyaningsih; Dona Budi Kharisma (Jurnal Penelitian Pendidikan IPA, 2023)
Currently, the world of education is the backbone of the development of Intellectual Property Rights (IPR). Research results in learning and research activities in the form of science and technology are objects of IPR that must be registered and protected. This is because the findings are an innovation that has high moral and economic value. This study aims to identify the role of IPR law in increasing the capacity of science education in Indonesia. This type of research is legal research using a conceptual approach. Data collection techniques were carried out using library research. Data analysis techniques were carried out using the critical hermeneutic method. The results of the study state that IPR law has two functions, namely: a protective function and an economic function. The function of protection means that the registration of IPR legally protects the findings of inventors as intellectual property. Inventors also have the right to sue other parties who use their findings without rights. The economic function means that registered innovations in science education can provide economic benefits for inventors as well as a source of income (royalty). However, the level of HKI registration in the world of science education is still low. The existence of HKI learning materials in science education is something that is needed at this time. Â